Wnt/β-catenin and notch signaling pathways in cardiovascular disease: Mechanisms and therapeutics approaches - Manizheh Azhdari; Axel zur Hausen (Pharmacological Research)
Wnt and Notch signaling pathways play crucial roles in the development and homeostasis of the cardiovascular system. These pathways regulate important cellular processes in cardiomyocytes, endothelial cells, and smooth muscle cells, which are the key cell types involved in the structure and function of the heart and vasculature. During embryonic development, Wnt and Notch signaling coordinate cell fate specification, proliferation, differentiation, and morphogenesis of the heart and blood vessels. In the adult cardiovascular system, these pathways continue to maintain tissue homeostasis and arrange adaptive responses to various physiological and pathological stimuli. Dysregulation of Wnt and Notch signaling has been involved in the pathogenesis of numerous cardiovascular diseases, including atherosclerosis, hypertension, myocardial infarction, and heart failure. Abnormal activation or suppression of these pathways in specific cell types can contribute to endothelial dysfunction, vascular remodeling, cardiomyocyte hypertrophy, impaired cardiac contractility and dead. Understanding the complex interplay between Wnt and Notch signaling in the cardiovascular system has led to the investigation of these pathways as potential therapeutic targets in clinical trials. In conclusion, this review summarizes the current knowledge on the roles of Wnt and Notch signaling in the development and homeostasis of cardiomyocytes, endothelial cells, and smooth muscle cells. It further discusses the dysregulation of these pathways in the context of major cardiovascular diseases and the ongoing clinical investigations targeting Wnt and Notch signaling for therapeutic intervention.